Kontribusi Pendapatan dari Usaha Pengolahan Ikan Asin terhadap Pendapatan Keluarga di Kecamatan Paloh Kabupaten Sambas - Saifullah; Januardy, Uray; Devi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
The processing of salted fish carried out by the people of Paloh District, Sambas Regency is a side income from fishing work carried out by housewives. The aims of this research are to calculate the costs, revenues, income, efficiency and income contribution of salted fish processing in Paloh District. The methods used are observation, interviews, questionnaires with primary and secondary data. The location was in Paloh District in Nibung and Sebubus Villages. The sampling technique was carried out by total sampling. The results of the research showed that the total cost value obtained for processing salted fish from 30 respondents was IDR. 8,734,510 with an average value of IDR 291,150,333. Total receipts amounted to Rp. 16,580,000 with an average value of Rp. 552,666,667. Total income is IDR 7,845,490 with an average of IDR. 261,516,333. The average efficiency value is 1.89821753 and the average value of revenue contribution is 13.5%.